Suicide and Lyme and associated diseases - Bransfield RC (Dove Medical Press, 2017)
Robert C Bransfield Department of Psychiatry, Rutgers-RWJ Medical School, Piscataway, NJ, USA Purpose: The aim of this paper is to investigate the association between suicide and Lyme and associated diseases (LAD). No journal article has previously performed a comprehensive assessment of this subject.Introduction: Multiple case reports and other references demonstrate a causal association between suicidal risk and LAD. Suicide risk is greater in outdoor workers and veterans, both with greater LAD exposure. Multiple studies demonstrate many infections and the associated proinflammatory cytokines, inflammatory-mediated metabolic changes, and quinolinic acid and glutamate changes alter neural circuits which increase suicidality. A similar pathophysiology occurs in LAD.Method: A retrospective chart review and epidemiological calculations were performed.Results: LAD contributed to suicidality, and sometimes homicidality, in individuals who were not suicidal before infection. A higher level of risk to self and others is associated with multiple symptoms developing after acquiring LAD, in particular, explosive anger, intrusive images, sudden mood swings, paranoia, dissociative episodes, hallucinations, disinhibition, panic disorder, rapid cycling bipolar, depersonalization, social anxiety disorder, substance abuse, hypervigilance, generalized anxiety disorder, genital–urinary symptoms, chronic pain, anhedonia, depression, low frustration tolerance, and posttraumatic stress disorder. Negative attitudes about LAD from family, friends, doctors, and the health care system may also contribute to suicide risk. By indirect calculations, it is estimated there are possibly over 1,200 LAD suicides in the US per year.Conclusion: Suicidality seen in LAD contributes to causing a significant number of previously unexplained suicides and is associated with immune-mediated and metabolic changes resulting in psychiatric and other symptoms which are possibly intensified by negative attitudes about LAD from others. Some LAD suicides are associated with being overwhelmed by multiple debilitating symptoms, and others are impulsive, bizarre, and unpredictable. Greater understanding and a direct method of acquiring LAD suicide statistics is needed. It is suggested that medical examiners, the Centers for Disease Control and Prevention, and other epidemiological organizations proactively evaluate the association between LAD and suicide. Keywords: depression, tick-borne, immune, homicidal, epidemiology, psychoimmunology